Persepsi Kemudahan Penggunaan Aplikasi Si AKU di Desa Wisata Candirejo Magelang - Ulqi Luqmatun Risqina; Mulyo Budi Setiawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Candirejo tourism village is a tourism located in Candirejo Village, Borobudur District, Magelang Regency, Central Java Province. This tourist village serves a variety of tour packages so that it gets many visits from people who want to travel, but for recording tour packages it still uses manual methods so there are obstacles in terms of recording. Seeing this, there needs to be a solution or solution to the problem. Through the Si AKU application, scientists furnish refreshes as well as arrangements fully intent on making it more straightforward for the Candirejo the travel industry town helpful to record visit bundles. This study utilizes a quantitative methodology with an information assortment strategy through comfort discernment surveys so fulfillment discernment values will be gotten as rates. From the calculation results, it was obtained that the Si AKU application obtained a perception assessment of 79.27% so that it can be concluded that through this application, the community, especially the Candirejo Tourism Village cooperative team, find it easier to record tour packages.